(untitled) (Scientific journal of the Fergana State University, 2025)
The article shows that the informal nature of online communication, the widespread use of slang, jargon, and the emphasis on visual content (pictures, videos, GIFs) in social networks, reduce the importance of all textual communication and increase the role of visual means of expression. Examples are given of how social networks allow users to create content, exchange ideas, and communicate online. The dynamic evolution of the language of social networks has led to the emergence of new words and phrases, and the transformation of old ones.